Eyes Wide Open: The Look of Obstinacy, the Gaze of the Camera, and the 24/7 Economy in Antja Ehmann and Harun Farocki’s Labour in a Single Shot (2011-2015) - Richard Langston (Studies in 20th & 21st Century Literature, 2016)
Moving beyond Jonathan Crary's ontologically framed subject in his essay 24/7, the following essay calls on Oskar Negt and Alexander Kluge's political economy of labor power in order to query the persistence of obstinacy within the neoliberal economy of 24/7. Tested against Harun Farocki's final film project co-produced with his wife Antje Ehmann, "Labour in a Single Shot," the essay argues that neoliberalism has in fact generated both tools and forms of collective agency that together call Crary's cultural pessimism into question.
Keywords: Jonathan Crary; Harun Farocki; Antje Ehemann; Alexander Kluge; Oskar Negt